Point-prevalence survey of hospital acquired infections in three acute care hospitals in Northern Nigeria - Abubakar, Usman (BioMed Central Ltd., 2020)
Background: Effective infection prevention and control strategies require reliable data describing the epidemiology of hospital acquired infections (HAIs), and this is currently lacking in Nigeria. The objective of this study was to evaluate the prevalence, types and risk factors associated with HAIs in acute care hospitals in Northern Nigeria. Methods: A pilot point-prevalence survey was conducted in three acute care hospitals in Northern Nigeria between April and May 2019 using the protocol developed by the European Centre for Disease Prevention and Control. Patients admitted into the wards at or before 8.00 am on the survey date were included. Patient’s medical records were reviewed by a clinical pharmacist with the support of the attending physician and nurse to identify HAIs. Results: Of the 321 patients surveyed, 50 HAIs were identified among 46 patients translating into a point-prevalence of 14.3%. The most common HAIs were bloodstream infection (38.0%), surgical site infection (32.0%) and pneumonia (12.0%). Neonatal (53.0%), pediatric surgical (26.7%) and surgical (10.1%) specialties had the highest prevalence. Device associated infections represented 16% of all HAIs including bloodstream infections and pneumonia. Of all the HAIs, 15 (30.0%) were present at the time of admission while 75.5% originated from the current hospitals. Univariate analysis showed that newborns (less than 1 month only) (OR: 4.687 95% CI: 1.298 – 16.927), intubation (OR: 3.966, 95% CI: 1.698 – 9.261), and neonatal (OR: 41.538 95% CI: 4.980 – 346.5) and pediatric surgical (OR: 13.091 95% CI: 1.532 – 111.874) specialties were significantly associated with HAI. Conclusion: The prevalence of HAI was relatively high compared to other developing countries and was significantly associated with neonatal and pediatric surgical specialties. Hospital infection control strategies should be strengthened to reduce the burden of HAIs.